ANALISIS KELAYAKAN PENGEMBANGAN E-HANDOUT BERBASIS PBL SEBAGAI SELF REGULATED LEARNING PADA MATERI VEKTOR - Aini, Addin Zuhrotul; Patmaningrum, Agustin; Yekti, Sherly Mayfana Panglipur; Etika, Erdyna Dwi; Pravangasta, Reza Dimas (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
The current curriculum emphasizes the use of technology in the learning process. Advances in science and technology have had a significant impact on the implementation of education. e-handout is a summary of learning material presented online which can help teachers and make it easier to deliver learning material so that learning objectives can be achieved as formulated. The aim of this research is to see the feasibility of developing PBL-based e-handouts with self-regulated learning on vector topics. This research is development research using the ADDIE model. The instrument used in this research is a questionnaire, namely a questionnaire to test the validity of material experts, language experts, and design experts. Based on the research results, it shows that material expert validation obtained an average of 91% with very feasible criteria, language expert validation obtained an average of 87.78% with very feasible criteria and based on the results of design expert validation obtained an average of 91.56% with very feasible criteria. . Thus, the development of PBL-based e-handouts with self-regulated learning on vector material has very good quality and is ready to be implemented more widely.